Identifikasi Senyawa Jamu Pegal Linu yang Beredar di Kabupaten Bantul dengan Metode Kromatografi Lapis Tipis - Furijika Fitriana Mosy; Kuswandani Kuswandani (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: Traditional herbal is not permitted to contain chemicals drug. It is possible allowed such as paracetamol and phenylbutazone.Objective: This study is aimed to identify the compounds of paracetamol and phenylbutazone in the traditional herbal of Jamu Pegal Linu (Herbal Medicine).Methods: This type of research was descriptive and the sample was determined by random sampling. The method used Thin Layer Chromatography (TLC) which is a physicochemical method. There were eight samples were extracted by the soxhletation method until a thick extract was obtained to be spotted in the quite phase of TLC silica gel F254. The motion phase used for the analysis of paracetamol was chloroform: acetone: toluene (65:25:10) and the motion phase for phenylbutazone analysis was benzene: chloroform: 96% acetic acid (50:40:10). Spots detection was done by observing under UV light of 254 nm and the spots that appeared were calculated for Rf value and compared with the standard Rf value of paracetamol and phenylbutazone.Results: The results obtained in this study were positive E samples containing paracetamol and phenylbutazone with Rf value of sample 0.57 and a standard Rf of paracetamol 0.57 and an Rf value of sample 0.82 and a standard Rf of phenylbutazone 0.86. The positive G sample contained paracetamol with a sample Rf value of 0.61 and a standard Rf value of paracetamol 0.68.Conclusion: From the eight samples of ‘Jamu Pegal Linu’, two of them were positive containing chemical drugs paracetamol and phenylbutazone.Keywords: Jamu Pegal Linu (Herbal Medicine), Paracetamol, Phenylbutazone, TLC